Fecal carriage and genetic characteristics of carbapenem-resistant enterobacterales among adults from four provinces of China - Li, Yuanyuan; Ma, Lan; Ding, Xinying; Zhang, Rong (Frontiers in Epidemiology, 2024)
Carbapenem-resistant Enterobacterales (CRE) is a global concern. This study investigated the prevalence of fecal colonization carriage and clonal dissemination of CRE among population in four provinces of China. A total of 685 stool samples were collected from four provinces in China. Among these samples,141 and 544 were obtained from healthy and hospitalized individuals, respectively. The overall fecal carriage rate was 9.6% (65/685) with 4.26% (95% CI: 0.9-7.6) in healthy individuals and 10.84% (95% CI: 8.2-13.5) in hospitalized patients. The highest prevalence was in Henan province (18.35%, 95% CI: 9%-18.7%). Sixty-six CRE isolates were identified in Escherichia coli (56.06%, 37/66), Klebsiella (15.15%, 10/66), Citrobacter (13.63%, 9/66), Enterobacter (12.12%, 8/66), and Atlantibacter (1.51%, 1/66). All CRE strains carried carbapenemase genes and multiple antibiotics resistance genes, blaNDM-5 (77.27%, 51/66) was the most common carbapenemase gene, followed by blaNDM-1 (19.69%, 13/66). Antibiotic resistance genes, including blaIMP-4, and the colistin colistin resistance (mcr-1) gene were also identified. All CRE isolates belonged to different sequence types (STs). ST206 (36.84%, 14/38) in E. coli and ST2270 (60%, 6/10) in Klebsiella were significantly dominant clones. The results indicated the prevalence of CRE fecal carriage among adults of China, mostly blaNDM-producing E coli, which pose significant challenges for clinical management. Screening for CRE colonization is necessary to control infection.